Digital Visualities and Materialities: paths for an anthropological walk - Ardèvol, Elisenda (2014)
This paper discusses digital technologies from an anthropological perspective, concentrating on ways in which cultural diversity, social inequality and the possibilities of change and social transformation have been discussed. We examine the ways in which the digital domain has been conceived, categories used to describe processes of change and continuity in everyday life, and the impact of digital technology on these. this approach leads us to question up how ethnographers have explored the relationships among local practices, global transits and digital technologies, and the material and visual aspects of the digital in cultural production and media communication. Finally, we discuss how to incorporate digital technologies in ethnographic practice and anthropological knowledge.